A report of recurrent ischemic stroke caused by premature atherosclerotic intracranial stenosis in a 26-year-old man with underlying cirrhosis, hypertension in the young and chronic kidney disease - Klinhom-on, Chaiwat; Udommongkol, Chesda (Journal of Thai Stroke Society, 2019)
The authors reported a 26-year-old Thai male military officer presenting with recurrent ischemic stroke. MRI showed multiple infarcts in bilateral subcortical areas in MCA territories and asymptomatic brain stem & middle cerebellar peduncle infarction. MRA revealed bilateral terminal ICA, proximal M1 MCA & A1 ACA stenosis whereas transcranial colour-coded sonography (TCCS) showed non-stenotic flow in all insonated arteries indicating normal hemodynamic circulation in pathological vessels. Co-morbidities were hypertension in young adult, chronic kidney disease and cirrhosis with occasional upper gastrointestinal hemorrhage exacerbating or worsening intracranial disease. After possible causes of stroke in young adults were investigated and showed negative, the most likely diagnosis was premature atherosclerotic intracranial stenosis complicated with multiple serious systemic diseases mimicking moyamoya syndrome which was not caused by moyamoya disease.